2022
DOI: 10.3138/ptc-2021-0081
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Pharmacological Cough Therapy for People with Interstitial Lung Diseases: A Case Report

Abstract: Purpose: To explore the feasibility of a non-pharmacological cough control therapy (CCT) customized for a client with interstitial lung disease (ILD). Client Description: An 83-year-old female with hypersensitivity pneumonitis, and chronic cough for 18 years treated previously with pharmacological treatment for the underlying lung disease and gastroesophageal reflux disease, as well as lozenges and breathing and relaxation strategies. Intervention: Four cough education and self-management sessions (45–60 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Observational and case studies have shown that multicomponent programmes consisting of education, vocal/laryngeal hygiene, hydration, cough control techniques, and psychoeducational counselling can help. These programmes can increase a patient's cough-related quality of life and empower them to take control over their cough [ 48 ].…”
Section: Symptom Relief and Supportive Care End-of-life Carementioning
confidence: 99%
“…Observational and case studies have shown that multicomponent programmes consisting of education, vocal/laryngeal hygiene, hydration, cough control techniques, and psychoeducational counselling can help. These programmes can increase a patient's cough-related quality of life and empower them to take control over their cough [ 48 ].…”
Section: Symptom Relief and Supportive Care End-of-life Carementioning
confidence: 99%